Anaerobic co-digestion of sewage sludge and trade wastes: beneficial and inhibitory effects of individual constituents - Berzal de Frutos, Olivia; Götze, Martin; Pidou, Marc; Bajón Fernández, Yadira (MDPI, 2023)
Anaerobic digestion (AD) of sewage sludge can be optimised by adding trade wastes (TWs) because of their nutrient content and boost in biogas formation if non-inhibitory. However, some components in TWs might have an inhibitory impact, such as nitrogen compounds, sulphate, heavy metals, metalloids, halogens and organic pollutants (e.g., phenol). This study aimed to understand the impact of TWs on the co-digestion with sewage sludge to identify appropriate TW loads for sustainable AD operation. The composition of 160 TWs was evaluated and the constituents with potential to cause inhibition or toxicity were tested in bio-methane potential (BMP) tests. The compounds studied in BMP tests included ammonia, zinc, copper, aluminium, mercury, arsenic, chloride, sulphate and nitrate. An improvement was observed at concentrations 2–746 mg Zn/L, 1066–2821 mg Cl/L as zinc sulphate and sodium chloride in biogas production, and 2–746 mg Zn/L, 162 mg SO4/L, 25 mg Hg/L as zinc sulphate, sodium chloride and mercury sulphate in methane production, respectively. Considering the TWs characterised and the results of the BMP tests, a volumetric ratio of 10/90 of TWs and sewage sludge is proposed as a suitable feedstock for co-digestion.
Keywords: inhibition; salts; counter-ions; biogas; kinetics; methane